Phenotypical, Clinical, and Molecular Aspects of Adults and Children With Homozygous Familial Hypercholesterolemia in Iberoamerica - Alves, Ana Catarina (2020)
Fil: Alves, Ana Catarina. Instituto Nacional de Saúde Doutor Ricardo Jorge, Lisboa; Portugal.